Evaluation of the impact of “speak out” and “human libraries” educational methodologies on nursing students' attitudes toward immigration - Gea-Caballero, Vicente; Pellín-Carcelén, Ana; Piera-Gomar, José Luís; Mármol-López, María Isabel; Santolalla-Arnedo, Iván; Tejada Garrido, Clara Isabel; Burgos-Esteban, Amaya; Rasal Sánchez, María; Rasal Sánchez, Amparo; Carboneres-Tafaner, María Inmaculada; Juárez-Vela, Raúl (Frontiers in Public Health, 2024)
Introduction Measuring and understanding attitudes toward migrants is crucial in Health Sciences professionals. Nursing students, as future professionals in the healthcare system, must be comprehensively trained and prepared from the undergraduate level to effectively face the challenges of caring for health and disease processes in an increasingly globalized world. Our study aims to determine the level of attitudinal change in nursing students for immigrants, based on a training intervention with sessions of coexistence with immigrants in Spain. Methods Quasi-experimental controlled and non-randomized study, carried out in 2019 in Nursing School La Fe, Valencia (Spain), with 201 participants (74 intervention group, 127 control group). Instrument: Attitudes toward Immigration Instrument (IAHI) questionnaire. Educational techniques of the training intervention: Speak outs and Human Libraries. Descriptive statistical analysis and comparison of results between groups was performed. Results The participants in the intervention group showed significant changes in attitude modification, both in the total score of the questionnaire and in 4 of the 5 dimensions (pre-post intervention medition). When comparing the differences between the intervention group and the control group, we observed significant differences in 3 of the 5 dimensions: equality principles and policies, positive favorability, and negative favorability. Conclussion Sessions involving coexistence, discussion, and reflection with immigrants, as educational intervention methods for nursing students (Speak outs and Human Libraries), are useful and effective tools to promote positive attitudinal changes toward immigrants within the healthcar context in nursing students.